Global Existence and Stability for Neutral Functional Evolution Equations with State-Dependent Delay - Baliki Abdessalam; Benchohra Mouffak (Nonautonomous Dynamical Systems, 2014)
In this paper we prove the global existence and attractivity of mild solutions for neutral semilinear evolution equations with state-dependent delay in a Banach space.